Pengembangan Media Video Virtual Reality Berbasis Camera Go Pro 360º dalam Pembelajaran Tari Lenggang Patah Sembilan di SMA Negeri 113 Jakarta Timur - Belinda Putri Amalya Pranoto; Triana, Dinny Devi; Cahyadi, Ojang (Jurnal Pendidikan Tari, 2022)
The purpose of this study was to determine how much influence the use of virtual reality video media based on the Go Pro 360º camera which is used as a dance learning medium for students and to assist the instructor as a new learning medium based on the Go Pro 360° camera, which is more efficient technology. This research is a Research & Development method with the ADDIE model (Analysis, Design, development, Implementation, Evaluation). The product resulting from this research is a virtual reality video based on the Go Pro 360º camera featuring the Lenggang Patah Sembilan dance. The results obtained from this study are based on material experts 100% "Fair"; media experts 42% “Fair enough”, 42% “Decent”, and 27% “Very Eligible; learning experts 34% “Fair”, 66% “Very Eligible”; and the results of media users (students) 50% “Eligible”, 50% “Very Eligible”. The conclusion in this study is that virtual reality videos based on the Go Pro 360º camera are worthy of being used as learning media in dance lessons, and can facilitate instructors in providing the learning process.